THE CULTURAL VALUE OF LEXICON IN â€œNGENDANGâ€ TRADITION - Fatimatuzzakrah, Fatimatuzzakrah; Suktiningsih, Wiya; Hastuti, Hilda (Kajian Linguistik dan Sastra, 2020)
AbstractOne of the most basic language capacities is the ability to express what the speaker sees, hears, feels, tastes, and kisses. Linguistic Anthropology is an interdisciplinary study of how language in a community is not only the logic of a linguistic system but also how speakers express something using language. The use of lexicon contains abstractions of cultural values and norms in the form of language which contain meaning, purpose and message. The purpose of this study is to identify the type and meaning of the lexicon as a tool used in the traditional event of ngendang. This research is descriptive qualitative. The data of this study were taken in the Batujai village - Praya using the interview method, observation and receiving information about the meaning of the lexicon as a tool used in the traditional event of Ngendang through informants. The researcher found 15 kinds of the tools used in traditional event of ngendang, and every tool has a lexicon that contains meaning, message and hope for sasaknese in Batujai village.Â Keywords: linguistic anthropologi, lexicon, ngendang, sasaknese, cultural values